The psychological, social and cultural experiences of undergraduate international students at the University of Limpopo (Turfloop Campus) : an afrocentric perspective - Hlokwe, Joy Katlego (University of Limpopo, 2019)
This research investigated the psychological, social and cultural experiences of undergraduate international students at the University of Limpopo (Turfloop Campus). The study was qualitative in nature with an exploratory research design. The research made use of purposive sampling. Data was collected through focus groups as it was an appropriate tool for collecting the in-depth experiences of international students registered at the University. There were four focus groups with six participants in each so the overall sample was twenty-four. The researcher sampled twelve females and twelve males to ensure gender representivity. Afrocentricity was used as theoretical framework underpinning the study. The data were analysed using Thematic content analysis (TCA). The following themes emerged out of an interpretation of data: Motivation; Discrimination; academic challenges; language barriers; sense of belonging; homesickness; avoidance, acculturation and shared African culture. International students experienced many challenges which resulted in loneliness and isolation. They also used negative defence mechanisms in order to cope in the new environment. Results indicated that there are divisions in terms of culture (both social and academic) in the University environment caused, in part, by the colonial partition of Africa. Conversely, elements of African culture that have survived the onslaught of colonialism (and in South Africa, apartheid) help bind international and peer host country students (and outside communities) together.
Thesis (M. A. (Psychology)) --University of Limpopo
Keywords: Undergraduate international students; Psychological, social and cultural experiences; Students, foreign; Foreign study; Affiliation (Psychology)